2010
DOI: 10.1002/lapl.201010062
|View full text |Cite
|
Sign up to set email alerts
|

Collision relaxation in 13CH3F with buffers

Abstract: Technique of delayed optical nutations is investigated from the viewpoint of possibility to measure collision relaxation rates in molecular gas by application of levels Stark switching. The numerical analysis enabled us to define the range of experimental parameters, at which the dependence of the delayed nutation signal on the duration of the Stark pulse becomes pure exponential, providing simple measuring tools. Experiments were performed at rotation transition R(4,3) of vibration band 0 ↔ 1 ν3 of polar gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Further, the measurements were interpreted to show that phase-changing collisions in the absence of state-changing ones, were also of low probability, so that the T 1 and T 2 lifetimes were the same. Much more recent work by Rubtsova et al 54,55 confirmed this result. Stark-shifting measurements are only possible on molecules possessing a dipole moment and degenerate or nearly degenerate levels of opposite parity, so cannot be applied to acetylene, for example, where the present results suggest…”
Section: Discussionmentioning
confidence: 66%
“…Further, the measurements were interpreted to show that phase-changing collisions in the absence of state-changing ones, were also of low probability, so that the T 1 and T 2 lifetimes were the same. Much more recent work by Rubtsova et al 54,55 confirmed this result. Stark-shifting measurements are only possible on molecules possessing a dipole moment and degenerate or nearly degenerate levels of opposite parity, so cannot be applied to acetylene, for example, where the present results suggest…”
Section: Discussionmentioning
confidence: 66%
“…The photon echoes formed in gases provide a large amount of data concerning the interatomic or intermolecular interactions (see, for example, [8][9][10]). One of the most rapid relaxation processes in gases is due to the elastic depolarizing collisions, which do not change the atomic velocities but give rise to the transitions between various Zeeman sublevels of atomic resonant levels [8].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of photon echo (and its multiple variations) since its first observation in 1964 in ruby [1] proved to be a versatile tool for the study of fast relaxation processes in various media, as well as for information storage and processing, including quantum information (see, for example, some recent papers [2][3][4][5] and [6,7]). The photon echoes formed in gases provide a large amount of data concerning the interatomic or intermolecular interactions (see, for example, [8][9][10]). One of the most rapid relaxation processes in gases is due to the elastic depo-larizing collisions, which do not change the atomic velocities but give rise to the transitions between various Zeeman sublevels of atomic resonant levels [8].…”
Section: Introductionmentioning
confidence: 99%
“…After the first experiment in a solid [1], the prediction of photon echoes in gases [2,3], and the first photon-echo observation in molecular gas [4], photon echo became of great importance in basic and applied research. Today the applications of photon echo concern the structure and dynamics of macromolecules [5], high-resolution spectroscopy of solids [6], local vibrations in disordered solids [7], and other fundamental research [8][9][10]. Photon echo generated by shaped femtosecond pulses of tunable radiation is one of the most promising tools for the investigation of ultrafast relaxation in condensed media [11].…”
Section: Introductionmentioning
confidence: 99%